INDIKATOR EKONOMI DAN ANGKA TUBERKULOSIS DI KABUPATEN KOTA DI JAWA BARAT - Sihaloho, Estro Dariatno; Alfarizy, Insan Lutfiana; Sagala, Endah Budiati (Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Tuberculosis, as the second deadliest infectious disease, has caused a total of estimated 1.6 million deaths in 2017 alone. Meanwhile, in West Java Province, Indonesia, a total of 59.833 people infected by Tuberculosis in 2017. This paper ‘s objective is to to estimate the effect of total poverty, total population, population density, total health workers, and GRDP on Tuberculosis cases in each cities and regency in West Java, Indonesia. This paper uses Random Effect Model with data of 27 cities and regencies in West Java Pronvice from 2014 to 2017 that collected from Badan Pusat Statistik (BPS) of West Java Pronvice. This paper uses total number of Tuberculosis cases as the dependent variable. As for the indenpendent variables, this paper uses total poverty, total population, population density, total health workers, and GDPR of each cities and regencies in West Java Pronvice. The result shows that total poverty, total population, and population density each has positive and significant effect on Tuberculosis cases in West Java Pronvice. While the total health workers and GRDP each has negative and significant effect on the Tuberculosis cases in West Java Pronvice.